Eagle vsDragon: Geostrategic Rivalry and Political Ambitions of the United States and China in Asia (Journal of Asian Development Studies, 2026)
At the dawn of the 21st century, the United States of America focus was on the continent of Asia region.US-China geo-strategic rivalry or competition had a “buzz word” that propagated bythe media, opinion makers and policy architects around the world. This research is titled Eagle vs. Dragon: Geostrategic Rivalry and Political Ambitions of the United States and China. It involves analysingthe dynamics of the US-China competition and its broader repercussions across Asia. The research will further examine the great power competition in the Asia region, where the two great powers compete for geostrategic advantage and to achieve national goals and objectives. China has confidence in achieving success, and the USA believes in victory, which will bring new challenges and opportunities for Asian regional nations. This research paper is firmly rooted in the realist tradition of International Relations and argues that both powers act as the main actors because of their national interests, security concerns, and aspirations to power, though in different ways and with distinct strategic approaches. The obstacle of this study will be attempting to discover the research, how the US-China Geostrategic competition impacts and shifts the dynamics of the Asian surface, especially in the Middle East, South Asia, Southeast Asia, Central Asia, and how both great powers secure the current challenges like (3ds) Debt, Data, and Dominance.Finally, the paper concludes that the US-China competition is altering regional balances and the world power structure, and that strategic rivalry is the hallmark of modern international politics, with dialogue, crisis management, and regional integration being the most effective measures to reduce the risks of conflict.